The BRICS response to COVID-19 - Fonseca, Pedro; Spellmann, Samuel; do Nascimento, Lucas Gualberto; Bastrykina, Elena; Das, Arindam (HAPSc Policy Briefs Series, 2020)
Since late 2019, SARS-CoV2 pandemic has spread worldwide. After several generations without a severe pandemic, the mixture of health and economic crisis has hit populations in all continents. The high degree of connectivity that States share, enabled by the current transportation and communication technologies, caused different regions of the world to be affected by coronavirus disease at almost the same time. Yet States responses to the SARS-CoV2 pandemic were not the same. This brief focuses on the BRICS countries individual, bilateral and collective responses to the international health crisis caused by coronavirus disease, from the early detection of COVID-19 cases in China in late December 2019 to the current surge of cases in Brazil.